PERAN BANK SAMPAH DALAM EFEKTIVITAS PENGELOLAAN SAMPAH (STUDI KASUS BANK SAMPAH MALANG) - Suryani, Anih Sri (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2014)
Waste Bank is one of many alternatives of waste management in Indonesia. Malang Waste Bank (Bank Sampah Malang - BSM) is a sample of Waste Bank that has been well established and widely used as a pilot project. This research conducted with qualitative method to analyse the effectiveness of waste management in BSM from the waste management perspective. From institutional perspective, cooperative system is considered to be quite effective in making BSM independent and self-sufficient. There are still many obstacles experienced in terms of financing, while in terms of regulation, a regulatory support is necessary to strengthen the performance of BSM. To date, public participation play significant role, although it has not been at its best. This is because knowledge and understanding on waste bank are not evenly distributed. Operational technique aspect has been carried out effectively, although location is still a major problem.